SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PEMILIHAN JURUSAN PADA UNIVERSITAS DENGAN MENGGUNAKAN METODE NAÏVE BAYES - Devina Ninosari; Kusrini Kusrini; M. Rudiyanto Arief (Informasi Interaktif, 2018)
In general, prospective new students are confused in choosing a department that suits the needs and abilities of the academic. Typically, the selection of majors is often chosen because the favorite departmental factors are mixed with prospective students' goals, costs and also not tested in the opinion so that later consequences will be found in the new student candidates because of wrong in choosing the majors are Stop college, Droup Out and leave and move majors. To facilitate the process of choosing the right majors and in accordance with the ability of prospective new students in choosing the department then the researcher will make the Decision Support System Support System Selection by using the Naïve Bayes Algorithm to find out new student candidates to be obtained the probability is accepted and not accepted. classify and acceptable and unacceptable decisions.From the results of calculations with naïve bayes algorithm for data samples 2016/2017 obtained 3 students. 1 in D3MI and 2 major in Inforatika Engineering and 7 people not accepted. After obtained the result of calculation by using 10 sample data hence the next researcher doing process accuracy level obtained in this research there is accuracy value equal to 70%.  Keywords: sistem Pendukung Keputusan, Pemilihan Jurusan, calon mhasiswa baru, Naïve Bayes.